2014
DOI: 10.1177/0954405413519434
|View full text |Cite
|
Sign up to set email alerts
|

Multi-objective optimization of upsetting parameters of Al–TiC metal matrix composites: A grey Taguchi approach

Abstract: This work is a novel attempt to identify the optimum process parameters in cold upsetting of Al–TiC metal matrix composites with multiple responses using grey Taguchi approach. The formation of barrel and workability are the important attributes that greatly influence the process of upsetting. Three independently controllable process variables, namely, aspect ratio, friction factor and load, each at four levels are considered to find their optimum levels which yields maximum barrel radius and workability simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…In case of hybrid aluminum matrix (HAMC) more than one reinforcements are added in aluminum matrix. Particles reinforced aluminum matrix composites are used in aerospace, automobile and structural application due very high strength to weight ratio, superior wear resistance, high stiffness, higher fatigue resistance controlled co-efficient of thermal expansion and better stability at elevated temperature, high thermal and electrical conductivity compared to conventional metals and alloys, which makes it suitable for design of an extensive range of components in advanced applications [1,2,[4][5][6][7]. Selection of processing of technique plays a vital role over the property of the composite.…”
Section: Introductionmentioning
confidence: 99%
“…In case of hybrid aluminum matrix (HAMC) more than one reinforcements are added in aluminum matrix. Particles reinforced aluminum matrix composites are used in aerospace, automobile and structural application due very high strength to weight ratio, superior wear resistance, high stiffness, higher fatigue resistance controlled co-efficient of thermal expansion and better stability at elevated temperature, high thermal and electrical conductivity compared to conventional metals and alloys, which makes it suitable for design of an extensive range of components in advanced applications [1,2,[4][5][6][7]. Selection of processing of technique plays a vital role over the property of the composite.…”
Section: Introductionmentioning
confidence: 99%
“…The parametric combination with highest GRG implies that the corresponding experimental run is closest to the optimal value of the desired multiple performance characteristics. 23 The GRG vector γ can be determined by equation (16) as follows. It is clearly observed that γ 1 has the largest value among the components of vector γ .…”
Section: Resultsmentioning
confidence: 99%
“…This method has been widely applied in recent years for optimal process parameter design of multiple performance characteristics. 1623 In the traditional machining, Kopac and Krajnik 24 applied the grey–Taguchi method to the robust design of flank milling parameters dealing with the optimization of the cutting loads, milled surface roughness, and the material removal rate. They obtained optimal parameter combination of coolant employment, number of end mill flutes, cutting speed, feed, axial depth of cut, and radial depth of cut.…”
Section: Introductionmentioning
confidence: 99%
“…Wear is a phenomenon of material removal that occurs in the interface between two surfaces, which affects the reliability and durability of any machine [1,2]. Whereas, the strength to weight ratio of the material directly affects the power consumption and efficiency of any mechanism [3].…”
Section: Introductionmentioning
confidence: 99%